Comparative study of Cr:Nd:YAG and Nd:YAG solar laser performances - Liang, Dawei (2021)
To improve the efficiency of Nd3+-doped YAG solar laser, cross-pumped Cr3+ and Nd3+ co-doped YAG ceramic material has attracted more attentions in recent years. The sensitizer Cr3+ ions have broad absorption bands in the visible region. Despite the interests in Cr:Nd:YAG ceramic medium, researchers have achieved significant laser efficiencies with different Nd:YAG single-crystal rods. While it is clear about the effectiveness of Nd:YAG single-crystal rods for solar laser operation, there still exist some concerns about the advantages of Cr:Nd:YAG ceramics in solar-pumped lasers. A 0.9 m diameter Fresnel lens is used as an economical solar collector. A 4 mm diameter, 25 mm length 1.0 at% Nd:YAG single-crystal rod and a 0.1 at% Cr: 1.0 at% Nd:YAG ceramic rod are pumped alternatively within a conical cavity through a secondary concentrator. With the Nd:YAG rod, the maximum laser power is 12.3 W, corresponding to 19.3 W/m2 collection efficiency. With the Cr:Nd:YAG ceramic rod, the maximum laser power is 13.5 W, corresponding to 21.2 W/m2 collection efficiency. This result is, to the best of our knowledge, the highest collection efficiency achieved with Cr:Nd:YAG ceramic medium. There is also a 109% increase in slope efficiency. In summary, we have experimentally observed a moderate, but not significant, advantage of Cr:Nd:YAG ceramics over Nd:YAG single-crystal medium in both solar laser conversion and slope efficiency.